ChemInform Abstract: Direct Trifluoroacetylation of Mono‐ and Disubstituted Thiophene Derivatives. Issue 14 (March 2016) - Andicsova‐Eckstein, Anita; Kozma, Erika; Puterova‐Tokarova, Zita; Vegh, Daniel
Abstract: Mono‐, bi‐, and tert‐thiophenes are conveniently trifluoroacetylated by one‐pot Friedel—Crafts reaction using TFAA as acylating agent.